Educación sexual y desarrollo emocional en los estudiantes de primero de bachilerato de la Unidad Educativa José María Velasco Ibarra, año 2019, Buena Fe - Saltos Briones, Karen Anabel (2019)
This research was entitled "Sexual education and emotional development in students of the first year of high school of the educational unit" José María Velasco Ibarra ". Through it, both teachers and parents were instructed on the importance of the relationship, sexual education and emotional development, during adolescence. Sex education refers to the set of activities related to teaching, dissemination and dissemination of human sexuality in all ages of development, with the aim of achieving a specific state of sexual and reproductive health and also a satisfactory state of health. general health, both physical and emotional. The objective was to determine the incidence of sex education in the emotional development of the students of the first year of high school of the Educational Unit "José María Velasco Ibarra", through a bibliographical study, statistical analysis and field study to develop an alternative proposal that contributes the improvement of sexual education and the emotional development of students. The theoretical foundation was constructed by means of the contents related to the variables defined in the problem. The research was based on a mixed approach, of feasible type, in which deductive and inductive methods were used, among others, being a descriptive and bibliographical field research in which observation techniques and surveys applied to teachers, parents of family and students of the first year of high school which support the results obtained throughout the process of the final report of the investigation.